2022
DOI: 10.14639/0392-100x-n1665
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune inflammation index in differentiated thyroid cancers

Abstract: SUMMARY Objective The aim of this study was to investigate the relationship between differentiated thyroid carcinomas (DTCs), histopathological findings and systemic immune-inflammation index (SII) [neutrophil (N) x platelet (P) / lymphocyte (L)] values. Methods 93 patients with DTC were included. N, P and L levels were measured, and the relationship between the SII and histopathological findings was determined. The results were compared with the values of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…It was first described as an indicator of prognosis in patients with resected hepatocellular carcinoma [9]. Subsequently, SII was shown to have prognostic value for various cancers [15][16][17][18][19][20][21][22]. Previous studies in adult patients with sepsis are consistent with our results [23,24].…”
Section: Discussionsupporting
confidence: 89%
“…It was first described as an indicator of prognosis in patients with resected hepatocellular carcinoma [9]. Subsequently, SII was shown to have prognostic value for various cancers [15][16][17][18][19][20][21][22]. Previous studies in adult patients with sepsis are consistent with our results [23,24].…”
Section: Discussionsupporting
confidence: 89%
“…The SII, another prognostic marker, was found to be higher in patients with thyroid cancer compared to healthy individuals in a study, but no correlation was found between lymph node involvement, invasion, and tumor size. [ 30 ] However, in another study, a relationship was found between lymph node involvement and SII. [ 31 ] In our study, no significant relationship was found between SII and tumor size, metastasis, and invasion in thyroid cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…Systemic immune-inflammation index (SII) is a composite index based on the absolute counts of neutrophils, lymphocytes, and platelets and has been found to be associated with the prognosis of several cancers. In a previous study, it was observed that the SII of patients with differentiated thyroid cancer was significantly higher when compared to a control group (6). Similarly, in a recent study, it has been reported that elevated neutrophil-lymphocyte ratio (NLR) values in patients with nodules can predict malignancy 11 .…”
Section: Introductionmentioning
confidence: 88%
“…In recent years, the hematological parameters have gained attention as potential markers to enhance the diagnosis and prognosis of various inflammatory conditions, including cancers [5][6][7][8][9][10][11][12] . Systemic immune-inflammation index (SII) is a composite index based on the absolute counts of neutrophils, lymphocytes, and platelets and has been found to be associated with the prognosis of several cancers.…”
Section: Introductionmentioning
confidence: 99%